Optimizing the Use of E-Worksheet and PHET Simulation in Science Learning during the Covid-19 Pandemic - Sunaryo Romli; Hera Nopiyanti; Eka Yustian Yusuf (Jurnal Pembelajaran Fisika, 2022)
This study examines the use of e-worksheets and PHET Simulation as virtual laboratories in science. This study aims to determine whether the use of PHET Simulation with e-worksheet guidance can optimize online learning to minimize learning loss due to the Covid 19 pandemic. E-worksheets are used as scaffolding media that are used to help guide students to do online practicums. The research was conducted in two stages. The first stage is conducting a direct trial of learning using PHET Simulation and e-worksheets through Google Classroom. For the second stage, the activities include collecting data using an accessibility questionnaire using a google form. The data were then analyzed by usability test covering aspects of usefulness, ease of use, ease of learning, and satisfaction. The usability test results show that the percentage of respondents to the questions given is dominated by the Agree (S) and Strongly Agree (SS) statements on all usability test indicators. This shows that the use of e-worksheets and PHET Simulation as a virtual laboratory fulfills the element of usability.Keywords: e-Worksheet, PHET simulation, Virtual laboratoryDOI: http://dx.doi.org/10.23960/jpf.v10.n1.202211